2016
DOI: 10.1073/pnas.1603872113
|View full text |Cite
|
Sign up to set email alerts
|

The adenovirus E4-ORF3 protein functions as a SUMO E3 ligase for TIF-1γ sumoylation and poly-SUMO chain elongation

Abstract: The adenovirus (Ad) early region 4 (E4)-ORF3 protein regulates diverse cellular processes to optimize the host environment for the establishment of Ad replication. E4-ORF3 self-assembles into multimers to form a nuclear scaffold in infected cells and creates distinct binding interfaces for different cellular target proteins. Previous studies have shown that the Ad5 E4-ORF3 protein induces sumoylation of multiple cellular proteins and subsequent proteasomal degradation of some of them, but the detailed mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…The E4-ORF3 SUMO target proteins have two distinct fates. One group (e.g., TFII-I and TIF-1c) is further degraded by the ubiquitin-proteasome pathway in the absence of any other viral proteins [77][78][79]. In contrast, degradation of the other group (e.g., Mre11 and Nbs1) is mediated by E1B-55K and E4-ORF6, but not by E4-ORF3.…”
Section: E4-orf3 and Regulation Of Protein Sumoylationmentioning
confidence: 98%
See 4 more Smart Citations
“…The E4-ORF3 SUMO target proteins have two distinct fates. One group (e.g., TFII-I and TIF-1c) is further degraded by the ubiquitin-proteasome pathway in the absence of any other viral proteins [77][78][79]. In contrast, degradation of the other group (e.g., Mre11 and Nbs1) is mediated by E1B-55K and E4-ORF6, but not by E4-ORF3.…”
Section: E4-orf3 and Regulation Of Protein Sumoylationmentioning
confidence: 98%
“…A comparative SUMO proteomic study revealed that SUMO conjugation of multiple host proteins increased upon Ad5 E4-ORF3 expression [72]. Biochemical studies using an in vitro SUMO-conjugation assay demonstrated that Ad5 E4-ORF3 functions as a SUMO E3 ligase [77]. Like ubiquitylation, sumoylation is carried out by a cascade of enzymatic steps [76].…”
Section: E4-orf3 and Regulation Of Protein Sumoylationmentioning
confidence: 99%
See 3 more Smart Citations